Prevalence of subclinical keratoconus and impact on adults undergoing routine, uncomplicated age-related cataract extraction - Tran, Tu M.; Mittal, Aman; Naik, Vihar; Chhadva, Priyanka; Wade, Matthew; Garg, Sumit (Frontiers in Ophthalmology, 2023)
Aim: To determine the prevalence of subclinical keratoconus (SKCN) among individuals undergoing routine, uncomplicated age-related cataract surgery and its impact on visual and refractive outcomes.Patient and Methods: At a major academic ophthalmology department in the United States, we reviewed records of patients aged 50 years and older who underwent surgery from January 2011 to June 2022. We excluded patients who had poor-quality or unreliable tomographic data, previous corneal surgery, keratorefractive procedures, and significant visionlimiting ocular pathology. We defined SKCN if an eye had a Belin-Ambrósio enhanced ectasia index (BAD-D) >1.7, which was based on the results of a meta-analysis of large studies. In addition to the BAD-D cutoff, the eye had to deviate significantly on at least one of seven additional parameters: 1) posterior elevation at thinnest point, 2) index of vertical asymmetry, 3) index of surface variation, 4) total front higher order aberrations, 5) front vertical coma, 6) front secondary vertical coma, 7) back vertical coma. An individual had SKCN if at least one eye met the tomography-based classification and did not have manifest KCN in either eye. Visual and refractive outcomes data were acquired from patients of one experienced cataract surgeon with cases done from July 2021 to June 2022. Statistical significance was set at p < 0.05.Results: Among 5592 eyes from 3828 individuals, the prevalence of SKCN was 24.7% (95% CI, 23.4 -26.1, 945 individuals), and the prevalence of KCN was 1.9% (95% CI, 1.6 -2.4, 87 individuals). The prevalence of SKCN did not increase with age and was more prevalent among females and non-white races. Median post-operative month one distance-corrected visual acuity (DCVA) and proportion of eyes with improvement in DCVA were similar between normal and SKCN eyes. The proportion of eyes reaching +0.5 and +1.0 diopter within the refractive target were similar between normal and SKCN eyes.Conclusions: SKCN is highly prevalent and should be detected but is unlikely to have a significant deleterious effect on outcomes of cataract surgery.